Functional Characterization of a Global Virulence Regulator Hfq and Identification of Hfq-Dependent sRNAs in the Plant Pathogen Pantoea ananatis - Shin, Gi Yoon; Schachterle, Jeffrey K.; Shyntum, Divine Y.; Moleleki, Lucy N.; Coutinho, Teresa A.; Sundin, George W. (Frontiers in Microbiology, 2019)
To successfully infect plant hosts, the collective regulation of virulence factors in a bacterial pathogen is crucial. Hfq is an RNA chaperone protein that facilitates the small RNA (sRNA) regulation of global gene expression at the post-transcriptional level. In this study, the functional role of Hfq in a broad host range phytopathogen Pantoea ananatis was determined. Inactivation of the hfq gene in P. ananatis LMG 2665T resulted in the loss of pathogenicity and motility. In addition, there was a significant reduction of quorum sensing signal molecule acyl-homoserine lactone (AHL) production and biofilm formation. Differential sRNA expression analysis between the hfq mutant and wild-type strains of P. ananatis revealed 276 sRNAs affected in their abundance by the loss of hfq at low (OD600 = 0.2) and high cell (OD600 = 0.6) densities. Further analysis identified 25 Hfq-dependent sRNAs, all showing a predicted Rho-independent terminator of transcription and mapping within intergenic regions of the P. ananatis genome. These included known sRNAs such as ArcZ, FnrS, GlmZ, RprA, RyeB, RyhB, RyhB2, Spot42, SsrA and 16 novel P. ananatis sRNAs. The current study demonstrated that Hfq is an important component of the collective regulation of virulence factors and sets a foundation for understanding Hfq-sRNA mediated regulation in the phytopathogen P. ananatis.